Design of Arabic Textbooks Based Flipping Book on Al-Masal (Proverbs) Material Class X MA - Anisatin, Luthfi; Afifah Akmalia; Asrori, Imam (UIN Raden Mas Said Surakarta, 2022)
The design of arabic textbooks based on flipping books is based on the existence of conventional textbooks that only focus on scientific development but students are not required to think critically. Furthermore, the existence of conventional books should be able to adjust the development of the digital era which certainly has an impact on students' interest in learning Arabic. This study aims to provide an overview of the material and items about al-Masal which is systematically designed so that students are able to think critically so that they can conclude al-Masal both orally and in writing, and is packaged with an interesting format, namely flipping books. This research is a development research using a three-D pattern (Define, Design, Develop). Based on the results of research and development, it is known that students' critical thinking ability can improve based on students being able to mention proverbs, explain proverbs, and apply proverbs orally and in writing. Then students' interest in learning will increase with the presentation of interesting teaching materials in the form of flipping books